Understanding of Dementia in the Polish Language: A Frame Semantic Approach - Maćkowiak, Maria; Libura, Agnieszka; Phillipson, Lyn; Szcześniak, Dorota; Rymaszewska, Joanna (Journal of Alzheimer's disease, 2023)
With the increasing incidences of dementia in aging societies, attention should be paid to the social context in which people with dementia live. One of its aspects is language transmitting beliefs, perceptions, and behavioral patterns. An analysis of understanding the diagnostic label of dementia may reveal the role of semantics in the process of social cognition of this disease. The overall aim of this study was to investigate the understanding of the word dementia (otępienie) in the Polish language. Frame semantics approach was applied. The structure of semantic information was uncovered with the concept of frame utilizing The National Corpus of Polish (the biggest corpus of contemporary Polish language of 1,500 million words). Additional data was collected from Polish speaking adults in Poland. The analyses allowed to identify the otępienie frame for Polish and verify how its elements are filled in by the general population, indicating the selectivity of colloquial knowledge about dementia. Dementia deviates from the prototypical disease. Need to care for the person with dementia outweighs treatment options. The cognitive symptoms and characteristics of the subject are salient. The perceptions of people with dementia embedded in semantics of the diagnostic label might create a basis for prejudicial attitudes among lay part of the society. Findings give foundation to further studies on relationship between semantics and social cognition of dementia which has a real impact on the social and clinical situation of people with dementia and may facilitate formulation of tailored messages aimed at building dementia-friendly society.